Stable Transmission in the Time-Varying MIMO Broadcast Channel. (23rd April 2008) - Anderson Anderson, Adam L. Adam L.; Zeidler Zeidler, James R. James R.; Jensen Jensen, Michael A. Michael A.
Abstract : Both linear and nonlinear transmit precoding strategies based on accurate channel state information (CSI) can significantly increase available throughput in a multiuser wireless system. With propagation delay, infrequent channel updates, lag due to network layer overhead, and time-varying node position or environment characteristics, channel knowledge becomes outdated and CSI-based transmission schemes can experience severe performance degradation. This paper studies the performance of precoding techniques for the multiuser broadcast channel with outdated CSI at the transmitter. Traditional channel models as well as channel realizations measured by a wideband channel sounder are used in the analysis. With measured data from an outdoor urban environment, it is further shown the existence of stable subspaces upon which transmission is possible without any instantaneous CSI at the transmitter. Such transmissions allow for consistent performance curves at the cost of initial suboptimality compared to CSI-based schemes.